CHANGING THE SPEED OF AN INDUCTION MOTOR BY RECALCULATING THE STATOR SLOTS - Komil G’afforov; Imomova Zilola; Khaydarov Sh. F. (Web of Journals Publishing, 2024)
Many mechanisms that perform common technological and production processes do not require smooth speed control. For them, procedures designed to adjust the speed in two or three steps will be sufficient. Such motors are made with several coils of different pairs of poles located on one stator slot, which allows you to change the number of pole pairs for a certain connection of coil sections. This article provides information about the structure and types of multi-speed asynchronous motors.
Keywords: Asynchronous motor, number of poles, multi-speed, frequency, torque, magnetic field.